Factors affecting adoption of improved maize seed and fertiliser in northern Tanzania - Nkonya, Ephraim M.; Schroeder, Ted; Norman, David (Wiley, 1997)
This study quantifies the socioeconomic factors that affect adoption of improved maize seed and chemical fertiliser by producers in Tanzania. A bootstrapped simultaneous equation Tobit model was used to analyse data obtained from a survey of 246 farmers in Northern Tanzania. The adoption of improved maize seed was positively affected by nitrogen use per hectare, farm size, farmer education attainment level, and visits by extension agents. Fertiliser adoption was positively related to the area planted with improved seed. Larger farms tended to use fertiliser less intensively than smaller farms. Results confirm the importance of recognising the heterogeneity of the farming population not only in terms of differences in the biophysical conditions but also in the socioeconomic, environmental conditions under which they operate. This has important implications in terms of developing different technologies and support systems that take such variation into account. The results also confirm the importance of focusing on producer education as a component in influencing technology and in accepting the concept of a technology ladder in designing technological packages and disseminating extension messages.